Spatial dynamics of the Argentine sandperch, Pseudopercis semifasciata (Pinguipedidae), in temperate rocky reefs from northern Patagonia, Argentina - Venerus, Leonardo Ariel (2013)
The choice of appropriate conservation strategies for reef fishes depends on their mobility, degree of site fidelity and residence times. Here we report the results of a small-scale mark–recapture and resighting study conducted to investigate the spatial dynamics of the Argentine sandperch, Pseudopercis semifasciata. This is the flagship species of the rocky-reef fish assemblage from northern Patagonia, which has been the target of uncontrolled fishing since the early 1950s. About 19% of the fish tagged were recaptured up to four years after tagging. In total, 180 of 218 recaptured fish stayed in the reef of tagging. Thirty-six of 57 recaptures made at known locations within popular fishing areas of San Jose ́Gulf, densely covered by patchy reefs, occurred within 100 m of the tagging site, up to 793 days after tagging. Six fish were recovered more than 1 km from where they were tagged. Smaller fish were more prone to relocate, and were recovered farther from the tagging site. Fish stayed in the reefs for periods longer than a year; larger males remained longer in the same reefs. Our results indicate that relatively small reserves (in the order of a few kilometres) could be effective at protecting P. semifasciata populations within the northern Patagonian gulfs.